Distribution of autobiographical memories: cultural life script account examined - Tartar, Elif Eda. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
The life script account of the distribution of autobiographical memories suggests that the culturally shared cognitive life scripts influence the encoding and retrieval of memories. Life scripts are argued to include positive events, mostly from late adolescence and early adulthood. The purpose of the present study was to investigate Turkish life scripts with different methodologies and to compare the cultural life script with the actual distribution of autobiographical memories. In Experiment 1, 247 participants estimated how old a hypothetical person was when s/he had been happiest, saddest, most fearful, most in love, most important and most traumatic experiences. In Experiment 2, 135 participants listed and evaluated seven important events that were likely to occur in the life of a newborn. In Experiment 3, 115 participants recalled autobiographical memories from different cue-words, their happiest, saddest, most fearful, most in love and most important and most traumatic autobiographical memories and their memories of three public events from their lifetime. Results revealed that there was a life script for Turkish culture which includes mostly positive transitional events from late adolescence and early adulthood, with a peak in early adulthood. However, although this script explains the recall of most important, most in love and happiest autobiographical memories, the distribution of cued-recall memories were not predicted by the cultural life script.
Keywords: Autobiographical memory.